Cohesive modeling of crack nucleation in a cylindrical electrode under axisymmetric diffusion induced stresses - Bhandakkar, Tanmay K.; Gao, Huajian (International journal of solids and structures, 2011)
We have recently modeled crack nucleation in a 2D strip electrode as localization of a periodic array of cohesive zones subject to diffusion induced stresses in an initially crack-free thin strip under galvanostatic solute insertion and extraction. Here we generalize this model to crack nucleation in a cylindrical electrode under axisymmetric diffusion induced stresses, focusing on the effect of the cylindrical geometry on the crack nucleation condition. Similar to our previous findings for the 2D strip geometry, the present analysis identifies a critical electrode size, typically in the nanometer range, to avoid crack nucleation.